The Impact of Closed Incision Negative Pressure Therapy on Postoperative Breast Reconstruction Outcomes. Issue 8 (August 2018) - Gabriel, Allen; Sigalove, Steven; Sigalove, Noemi; Storm-Dickerson, Toni; Rice, Jami; Maxwell, Patrick; Griffin, Leah
Abstract : Background: Studies report that incision management with closed incision negative pressure therapy (ciNPT) may provide clinical benefits, including protecting surgical incisions, for postsurgical closed incisions (eg, orthopedic, sternotomy, and colorectal). This retrospective analysis compared postoperative outcomes in patients who received ciNPT versus standard of care (SOC) for incision management after breast reconstruction postmastectomy. Methods: Patient demographics, chemotherapy exposure, surgical technique, ciNPT use, number of drains, time to drain removal, and 90-day postoperative complication rates were analyzed from records of 356 patients (ciNPT = 177, SOC = 179) with 665 closed breast incisions (ciNPT = 331, SOC = 334). Results: Overall complication rate was 8.5% (28/331) in ciNPT group compared with 15.9% (53/334) in SOC group ( P = 0.0092). Compared with the SOC group, the ciNPT group had significantly lower infection rates [7/331 (2.1%) versus 15/334 (4.5%), respectively; P = 0.0225], dehiscence rates [8/331 (2.4%) versus 18/334 (5.4%), respectively; P = 0.0178], necrosis rates [17/331 (5.1%) versus 31/334 (9.3%), respectively; P = 0.0070], and seroma rates [6/331 (1.8%) versus 19/334 (5.7%), respectively; P = 0.0106]. The ciNPT group required significantly fewer returns to operating room compared with the SOC group [8/331 (2.4%) versus 18/334 (5.4%), respectively; P = 0.0496]. Time to complete drain removal per breast for ciNPT versus SOC groups was 9.9 versus 13.1 days ( P < 0.0001), respectively. Conclusions: Patients who received ciNPT over closed incisions following postmastectomy breast reconstruction experienced a shorter time to drain removal and significantly lower rates of infection, dehiscence, necrosis, and seromas, compared with the SOC group. Randomized controlled studies are needed to corroborate the findings in our study.